Always Ascending (But Sometimes Descending): Striving for the Garden of Eden in the African Hebrew Israelite ‘Village of Peace’ - Markowitz, Fran (Journal for the study of religion, nature and culture, 2025)
This research explores the African Hebrew Israelite Community (AHIC)’s ongoing bond with the Land of Israel which they see as part of their program for a divinely inspired Edenic lifestyle. Based on long-term ethnographic engagements, our research focuses on community members’ use of a discursive trope that we call ‘ascending-descending’. This terminology, we argue, is both flexible and failure-proof, as it allows the AHIC to present themselves as Edenic and agrarian as well as modern, while also explaining their unsuccessful attempts at living off the land as the result of human fallibility. We also note an ongoing commitment within Hebrew Israelite theology to God’s plan that they believe can never fail, as well as to promises of earthly salvation and eternal life that continue to compel members of the AHIC to seek new and yet unrevealed paths to the Garden of Eden.